2008
DOI: 10.1590/s0034-71672008000700020
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da Hanseníase: relato de experiência de acadêmicos de enfermagem

Abstract: RESUMO RESUMO RESUMO RESUMO RESUMO O Brasil é o segundo no mundo em novos casos de hanseníase. O controle da doença continua sendo uma meta desafiante. Buscou-se descrever o perfil morfológico de lesões cutâneas e outras seqüelas e analisar a conduta adotada no cuidado de feridas de um grupo de pessoas com seqüelas de hanseníase asiladas em uma instituição não governamental. A experiência de ensino-aprendizagem foi longitudinal, fundamentada na Metodologia Científica da Assistência de Enfermagem, envolvendo pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 3 publications
1
4
0
11
Order By: Relevance
“…The degree of disability is determined from the neurological evaluation of the eyes, hands and feet, and the result is expressed in values ranging from 0 to II. Degree 0 means there is no neural impairment while degree I indicates loss of sensitivity and II indicates the presence of disabilities and deformities (Pereira et al, 2008;Monteiro et al, 2014;Barbosa, Freitas, 2017). The present study showed that the majority of the patients showed degree 0 of impairment after physical incapacity evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of disability is determined from the neurological evaluation of the eyes, hands and feet, and the result is expressed in values ranging from 0 to II. Degree 0 means there is no neural impairment while degree I indicates loss of sensitivity and II indicates the presence of disabilities and deformities (Pereira et al, 2008;Monteiro et al, 2014;Barbosa, Freitas, 2017). The present study showed that the majority of the patients showed degree 0 of impairment after physical incapacity evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Essas incapacidades têm sido ponderadas pelo estigma e pela discriminação dos pacientes, portanto Pereira et al 20 relatam que uma das formas mais eficazes de determinar se o diagnóstico tem sido precoce é identificando a presença de incapacidades físicas no momento da diagnose. O grau de incapacidade é determinado a partir da avaliação neurológica dos olhos, das mãos e dos pés, e o seu resultado é expresso em valores que variam de zero a dois, sendo zero se não houver comprometimento neural; um para diminuição ou perda da sensibilidade e dois para presença de incapacidades e deformidades 21 . Em relação à avaliação da incapacidade, os dados deste estudo demonstraram que a maioria dos pacientes apresentou, por ocasião do diagnóstico, grau zero de incapacidade física, fato este que entra em consonância com uma pesquisa realizada no município de Montes Claros.…”
Section: Discussionunclassified
“…30,8 Following controversial patterns the results presented, physiopathological gravity of leprosy justifies the presence of cutaneous ulcers resulting from serious physical disabilities compromising, so the functional capacity of individuals sick and consequently your QOL. 7,31 The process of illness associated with chronic diseases encourages the development of motor disabilities, psychological and social, limiting individuals and directly affecting their quality of life. When we refer to leprosy, this condition worsens, favoring social isolation, loss laborativas and therefore difficulty of acceptance of the process of illness and self-care, causing distress with repercussions on personal and professional life.…”
Section: Discussionmentioning
confidence: 99%